Top-down fabrication of GaN nano-laser arrays by displacement Talbot lithography and selective area sublimation. (27th March 2019) - Damilano, Benjamin; Coulon, Pierre-Marie; Vézian, Stéphane; Brändli, Virginie; Duboz, Jean-Yves; Massies, Jean; Shields, Philip A.
Abstract: We show that a 4 μ m thick GaN layer grown by metal-organic vapour phase epitaxy can be transformed into a well-organized array of GaN nanowires (NWs) using displacement Talbot lithography and selective area sublimation. The optical quality of the GaN NWs obtained by this method is attested by their room temperature photoluminescence and the observation of lasing under optical pumping with a minimum excitation power density threshold of 2.4 MW cm −2 .